2016
DOI: 10.21549/ntny.15.2016.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Munka- és élet-értékváltozások iskolaelhagyók körében

Abstract: A tanulmány azt a célt szolgálja, hogy alapot nyújtson egy lemorzsolódást jelző rendszernek a kidolgozásához. A bemutatott vizsgálat rész – mely egy komplex kutatás egyik komponense csupán – célja, hogy feltárja az is – kolai lemorzsolódás és az újratanulás időszakára jellemző értékváltozásokat és hangulatingadozásokat. A vizsgálatok középpontjában olyan fiatalok álltak, akik bár elszenvedték és átélték az általános iskolai vagy szakképzésből történő lemorzsolódást, újra képesek voltak iskolapadba ülni, és fel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…With regard to further study after the university, respondents considered a number of reasons (Table 5), but in principle, the reason for continuing their studies was not to get away with work. These results partly confirm and complement the conclusions of Csehné Papp (2013, 2016). The results of previous research have shown that, on the one hand, the majority of students decide to continue their studies after completing their bachelor's degree, and on the other hand, the quality of the education they receive has a strong influence on their intention to continue.…”
Section: Summary and Concluding Remarkssupporting
confidence: 90%
See 1 more Smart Citation
“…With regard to further study after the university, respondents considered a number of reasons (Table 5), but in principle, the reason for continuing their studies was not to get away with work. These results partly confirm and complement the conclusions of Csehné Papp (2013, 2016). The results of previous research have shown that, on the one hand, the majority of students decide to continue their studies after completing their bachelor's degree, and on the other hand, the quality of the education they receive has a strong influence on their intention to continue.…”
Section: Summary and Concluding Remarkssupporting
confidence: 90%
“…Hence, the main task of universities and colleges is to provide self-initiated education. Several authors (Csehné Papp. 2013, 2016; Dosi et al ., 2006) stress the importance of the relation between education and the labour market.…”
Section: Theoretical Overviewmentioning
confidence: 99%
“…A tradicionális felfogás ezt tekinti a nők elsődleges szerepének, és ennek következtében a munkaerő-piacon már csak másodlagos szereplőkként bánnak velük. 10.18531/Studia.Mundi.2017.04.01.69-81 A nyolcvanas években a volt szocialista államok körében a nők gazdasági aktivitása jelentősen magasabb volt Nyugat-Európa országaihoz képest, munkaerő-piaci részvételük messze felülmúlta a fejlett nyugati piacgazdaságokét (Csehné, 2012). A rendszerváltást követő időszakban azonban a nők foglalkoztatottsága jelentősen visszaesett, a munkanélküliség látványosan nőtt.…”
Section: Bevezetésunclassified